A moderated mediation analysis of the effects of the COVID-19 pandemic on well-being and sport readiness of Italian team sports players: The role of perceived safety of the training environment - Vitali, F.; Bisagno, E.; Coco, M.; Cadamuro, A.; Maldonato, N. M.; Di Corrado, D. (International Journal of Environmental Research and Public Health, 2022)
Background: The protective restrictions (e.g., lockdowns, quarantines, social and physical distancing) consequent to the global pandemic caused by COVID-19 posited new challenges to athletes practicing competitive team sports. This study aimed to gain an understanding of the impact of the ongoing COVID-19 pandemic on the well-being and sports readiness to train and to compete of competitive female and male athletes practicing outdoor (i.e., rugby, soccer) and indoor (i.e., volleyball, basketball) team sports who were active during the Italian first and second waves of COVID-19. Methods: An online survey assessing demographic characteristics, perceived safety of the training environment, COVID-19 risk, fear of COVID-19, well-being, and sport (training and competition) readiness was administered to 619 team sports players. We examined differences by gender, previous COVID-19 experience, and team sport setting (i.e., outdoor vs. indoor). A moderated mediation analysis was conducted to assess the impact of perceived COVID-19 risk and fear of COVID-19 on athletes` well-being and sports readiness, using perceived safety of the training environment as a mediator and gender and sport setting as moderators. Results: Indoor team sports and female athletes showed higher perceived COVID-19 risk, while athletes with no-COVID-19 experience reported higher fear of COVID-19. Perceived COVID-19 risk (directly and via perceived safety of the training environment) and fear of COVID-19 were negatively associated with athletes` well-being and sports readiness. Conclusions: This study highlighted an understanding of the psychological implications of the COVID-19 pandemic, emphasizing the role of the perceived safety of the training environment on athletes` well-being and sports readiness. Future studies may advance safety-based interventions to promote well-being and a safer return to sport.